"I Learn to Seek Solution but Without Work I Can't Solve Anything" Youth Education and Community Development in Rural Honduras [Sample] (2016)
This paper draws on a social capital framework to explore the complex relationship between youth education, their roles in community development, and their future opportunities as they transition from school to work against the backdrop of the social, economic, and political realities of rural Honduras. Data is from a three-year qualitative study that followed a cohort of 6th grade students as they progressed through the Sistema de Apprendizafe Tutorial (SAT), an alternative secondary education program that facilitates the development of capabilities so that youth can take charge of their intellectual and spiritual growth and contribute to the building of better communities.
we focus on the youths' own words to understand how they conceptualize the resources that exist in their communities, their access to these resources, when and how these resources are successfully mobilized for community development, as well as how youth perceive their limitations to create future opportunities, particularly with regards to work.
Keywords: Educational development